A genome-wide strategy to identify causes and consequences of retrotransposon expression finds activation by BRCA1 in ovarian cancer. Issue 1 (6th January 2021) - Alkailani, Maisa; Palidwor, Gareth; Poulin, Ariane; Mohan, Raghav; Pepin, David; Vanderhyden, Barbara; Gibbings, Derrick
Abstract: It is challenging to identify the causes and consequences of retrotransposon expression in human disease due to the hundreds of active genomic copies and their poor conservation across species. We profiled genomic insertions of retrotransposons in ovarian cancer. In addition, in ovarian and breast cancer we analyzed RNAs exhibiting Bayesian correlation with retrotransposon RNA to identify causes and consequences of retrotransposon expression. This strategy finds divergent inflammatory responses associated with retrotransposon expression in ovarian and breast cancer and identifies new factors inducing expression of endogenous retrotransposons including anti-viral responses and the common tumor suppressor BRCA1. In cell lines, mouse ovarian epithelial cells and patient-derived tumor spheroids, BRCA1 promotes accumulation of retrotransposon RNA. BRCA1 promotes transcription of active families of retrotransposons and their insertion into the genome. Intriguingly, elevated retrotransposon expression predicts survival in ovarian cancer patients. Retrotransposons are part of a complex regulatory network in ovarian cancer including BRCA1 that contributes to patient survival. The described strategy can be used to identify the regulators and impacts of retrotransposons in various contexts of biology and disease in humans.